Voriconazole Induced Hallucinations and Visual Disturbances in a Female Child: A Case Report and Literature Review - Rujiang Zheng; Yu Li; Chuyi Guo; Yuxin Pei; Zhiyong Ke; Libin Huang (Frontiers Media S.A., 2021)
Voriconazole is a second-generation azole widely used for the prevention and treatment of fungal infection in leukemia patients. We report a case of 9-year-old girl with T-cell acute lymphoblastic leukemia who developed hallucinations and visual disturbance after using voriconazole twice. These symptoms began acutely after treatment with voriconazole and resolved rapidly when the voriconazole was stopped. No specific cause was identified, and thus the symptoms were considered to be the adverse drug reactions (ADRs) of voriconazole. Simultaneous development of hallucinations and visual disturbance caused by voriconazole in children rarely have been reported before and the causes of these ADRs are unknown. Several other cases of hallucinations and (or) visual disturbance caused by voriconazole among 15-81 years old patients have been reported in the literature, and are reviewed. Those patients reminded us of the importance of being aware of hallucinations and visual disturbance associated with voriconazole treatment. In addition, we speculate that the hallucinations and visual disturbance are not related to the dosage form of voriconazole. We emphasize that it is also important to monitor the concentration of voriconazole regularly to avoid potential toxicity.